The Influence of Management Accounting Information Systems and Performance Measurement on Managerial Performance with Human Capital as an Intervening Variable - Purwatiningsih Purwatiningsih; Silvia Sari (CV. Ulil Albab Corp, 2026)
This study aims to examine the influence of Management Accounting Information Systems and Performance Measurement on Managerial Performance, with Human Capital as an Intervening Variable. This research is quantitative, associative (causal), and the population is MSMEs in Depok City. The sample was determined using the Slovin formula, resulting in a total sample of 100. The data analysis technique used was Structural Equation Modeling (SEM) using the SmartPLS data processing program. The results indicate that there is an influence of Management Accounting Information Systems on human capital, an influence of performance measurement on human capital, an influence of Management Accounting Information Systems on managerial performance, an influence of performance measurement on managerial performance, and an influence of Human Capital on managerial performance. Human capital mediates the influence of Management Accounting Information Systems on managerial performance, and human capital mediates the influence of performance measurement on managerial performance in MSMEs in Depok City.